Performance and evaluation of calcium carbide residue stabilized lateritic soil for construction materials - Prinya Chindaprasirt (2020)
© 2020 This research investigated the engineering properties of lateritic soil stabilized with calcium carbide residue (CCR), which is a by-product of an acetylene production process. The strength, modulus of elasticity and California Bearing Ratio of the stabilized soil were tested in both soaked and un-soaked conditions. The specimens were compacted under modified Proctor at optimum water content. Test result showed that the engineering properties of lateritic soil stabilized with CCR developed significantly over curing time, confirming the reaction between the calcium hydroxide in CCR and the pozzolanic material in the clay component of lateritic soil. The engineering properties of the un-soaked samples were higher than those of the soaked samples indicating the optimum water content was sufficient for the hydration reaction. The normalized engineering properties showed unique linear relationship when plotted against the log of curing time. This indicated that the pozzolanic reaction in CCR stabilized lateritic soil samples was the main factor for the engineering properties development in both un-soaked and soaked conditions. The unique linear relations could be used for the design for strength, modulus of elasticity and California Bearing Ratio of the stabilized soil.